Friction stir additive manufacturing method for titanium alloy components with nano-scale fine grain structure

Through hydrogen treatment, solid solution treatment and isometric angle extrusion treatment, combined with the friction stir additive manufacturing process, the problem of columnar crystals in the titanium alloy metallurgical structure in the prior art is solved, and the nanoscale fine grain structure and good mechanical properties of titanium alloy members are achieved.

CN116275457BActive Publication Date: 2025-02-25NANJING TECH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310243092.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-14
Publication Date
2025-02-25
Estimated Expiration
2043-03-14

AI Technical Summary

Technical Problem

When existing additive manufacturing technology processes titanium alloys, it is easy to lead to significant columnar crystal structure with metallurgical structure, which will affect the overall performance and service performance of titanium alloy components.

Method used

The titanium alloy rod material with hydrogen placement treatment, solution treatment and equal diameter extrusion treatment is used as raw materials, and the friction stir additive manufacturing process is used to deposit layer by layer, annealing and hydrogen removal heat treatment is carried out to obtain a titanium alloy member with nano-scale fine grain structure.

Benefits of technology

The formation of nano-scale fine grain structure of titanium alloy components is achieved, which reduces processing difficulty, improves the stability of tissue performance, and effectively retains nanocrystals, improving the mechanical properties of titanium alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116275457B_ABST
    Figure CN116275457B_ABST
Patent Text Reader

Abstract

The present invention provides a friction stir additive manufacturing method for a titanium alloy component with a nano-scale fine grain structure, comprising the following steps: subjecting a first titanium alloy rod to a hydrogen treatment and a solid solution treatment in sequence to obtain a second titanium alloy rod; subjecting the second titanium alloy rod to an equal-diameter angular extrusion treatment to refine the grain size of the titanium alloy to a first nano-grain interval to obtain a third titanium alloy rod; using the third titanium alloy rod as a raw material, adopting a friction stir additive manufacturing process, depositing layer by layer in an upward growth manner from the first layer according to a preset program until the last layer is deposited to obtain a titanium alloy component intermediate; subjecting the titanium alloy component intermediate to annealing and dehydrogenation heat treatment to obtain a titanium alloy component with a nano-scale fine grain structure, and the grain size of the titanium alloy is within the second nano-grain interval. The method of the present invention reduces the difficulty of processing, and the obtained titanium alloy structure performance is more stable, and the nanocrystals are well retained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of additive manufacturing, and in particular to a friction stir additive manufacturing method for a titanium alloy component with a nano-scale fine grain structure. Background Art

[0002] Common types of heat sources used in additive manufacturing include laser, arc, plasma, electron beam, etc. In this type of melting additive manufacturing process, the metal micro-area is rapidly heated under the action of a concentrated heat source, rapidly cooled and solidified, and then undergoes multiple cycles, variable cycles, intense heating and cooling during the layer-by-layer deposition process. Adjacent layers or several layers undergo cyclic remelting and cooling, and other deposited layer grains are cyclically micro-heat treated. This process can easily cause the metallurgical structure to present a significant columnar crystal structure. This process can easily cause the metallurgical structure to present a significant columnar crystal structure. When the raw material is titanium alloy, in the additive manufacturing process using high-energy and highly concentrated laser beams such as laser selective melting and laser deposition forming, most of the grains grow perpendicular to the substrate interface into coarse original β grains and columnar crystals, with only a small amount of equiaxed or fine grains at the bottom and top, forming extremely uneven organizational characteristics. This coarse organization even develops into through-columnar crystals in additive processes with higher energy density, which seriously affects the comprehensive performance of titanium alloy components and their application in load-bearing structures. At the same time, the above-mentioned manufacturing process will also cause macro-microscopic organizational inhomogeneity and many metallurgical defects, such as pores and microcracks, which affect the service performance of titanium alloy components.

[0003] Grain refinement is one of the important ways to strengthen metal materials. The Hall-Petch theoretical formula gives a quantitative description of the strengthening effect. Its internal mechanism is that the finer the grains, the more grain boundaries there are, the greater the resistance to dislocation movement, the finer the grains, the smaller the stress concentration, the less likely cracks to initiate and propagate, and the better the fracture toughness. Traditional experience shows that plastic deformation is the most promising and effective way to achieve simultaneous improvement of organization and defects. Traditional structures often go through processes such as casting-forging / rolling to achieve organization refinement and deformation toughening. The nano-structured material performance is significantly improved through severe plastic deformation. Therefore, it is of great significance to achieve ultrafine crystallization and nano-structured additive manufacturing organizations.

[0004] To this end, domestic and foreign scholars have introduced plastic deformation into additive manufacturing, and used micro-rolling, micro-forging and other methods to control the organization. Martina et al. in the UK, Yanshan University, Northeastern University and others introduced high-pressure roller online rolling in the arc wire feeding process, and the columnar crystals of titanium alloy were significantly refined to 56-139μm; Professor Zhang Haiou of Huazhong University of Science and Technology developed an intelligent micro-casting, forging and milling composite manufacturing technology with arc and plasma beam as heat sources, and achieved certain results; Xi'an Jiaotong University, Yanshan University, Shenyang Aerospace University and others used point forging, process hammering and other methods to introduce plastic deformation and achieved certain results.

[0005] Plastic deformation and its recovery and recrystallization refinement are important solutions for additive manufacturing, but the amount of deformation is currently significantly insufficient, especially for titanium alloys. Conventional plastic deformation processing produces poor grain refinement and it is difficult to obtain nanocrystals. Therefore, the process of improving the structure of titanium alloys in additive manufacturing and retaining it in the components needs to be explored urgently. Summary of the invention

[0006] The purpose of the present invention is to address the deficiencies in the prior art and provide a friction stir additive manufacturing method for a titanium alloy component with a nano-scale fine-grained structure. The method uses a titanium alloy rod that has been subjected to hydrogen treatment, solution treatment and equal-diameter angular extrusion treatment in sequence as a raw material, and combines the friction stir additive manufacturing process to directly obtain a titanium alloy component with a nano-scale fine-grained structure. The processing difficulty is reduced, the titanium alloy structure performance is more stable, and the nanocrystals are well retained.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A friction stir additive manufacturing method for a titanium alloy component having a nano-scale fine grain structure comprises the following steps:

[0009] The first titanium alloy rod is subjected to hydrogen treatment and high temperature solution treatment in sequence to obtain a second titanium alloy rod;

[0010] The second titanium alloy rod is subjected to equal-channel angular extrusion processing to refine the grain size of the titanium alloy to a first nano-grain range, thereby obtaining a third titanium alloy rod;

[0011] Using the third titanium alloy rod as a raw material, a friction stir additive manufacturing process is adopted, and deposition is performed layer by layer in an upward growth manner starting from the first layer according to a preset program until the last layer is deposited, thereby obtaining a titanium alloy component intermediate;

[0012] Annealing and dehydrogenation heat treatment are performed on the titanium alloy component intermediate to obtain a titanium alloy component with a nano-scale fine grain structure, and the grain size of the titanium alloy is within the second nano-grain range;

[0013] Among them, hydrogen treatment and solid solution treatment reduce the processing stress of titanium alloy and improve the stability of titanium alloy structure.

[0014] In an optional manner, the first nano-grain interval is (200nm, 500nm].

[0015] In an optional manner, the second nano-grain interval is [50nm, 200nm].

[0016] In an optional manner, the specific process of hydrogenation treatment includes:

[0017] The first titanium alloy rod is placed in a tubular hydrogen heat treatment furnace and vacuumed to 1.5*10 -3 Pa, heat to 700°C-800°C at a rate of 10-20°C / min, keep warm for 10-30min, then fill with 0.1-0.8% hydrogen according to the weight percentage of the titanium alloy rod, keep warm for 1-4h, and then cool to room temperature at a rate of 5-15°C / min.

[0018] In the optional method, the specific process of high temperature solution treatment includes:

[0019] The first titanium alloy rod after hydrogen treatment is placed in a heat treatment furnace and heated at a rate of 10-20°C / min to the titanium alloy phase transition temperature T p ℃+10℃, keep warm for 20-40min, and then quickly cool to room temperature by water cooling to obtain the second titanium alloy rod.

[0020] In an optional manner, the specific process of equal channel angular extrusion processing includes:

[0021] The second titanium alloy rod is preheated to 600°C at a rate of 10-20°C / min and kept warm for at least 20 minutes. The equal-diameter angular extrusion die is heated to 350°C at a rate of 10-20°C / min, and the preheated second titanium alloy rod is immediately transferred to the equal-diameter angular extrusion die. The second titanium alloy rod is extruded in one pass at a rate of 5-10 mm / s under the extrusion action of the die.

[0022] In an alternative approach, the inner corner of the mold is used The die with a range of 90 to 130° and a die external angle ψ of 0 to 30° is subjected to equal-diameter angular extrusion.

[0023] In an optional manner, the process parameters of the friction stir additive manufacturing include:

[0024] Stirring head forward speed: 100~2000mm / min; Stirring head rotation speed: 500~3000r / mm; Feeding speed: 1~200mm / min; Stirring head downward pressure: 10~500KN; Stirring head pressure: 0.1~10mm.

[0025] In an optional manner, the specific process of annealing and dehydrogenation heat treatment includes:

[0026] Put the titanium alloy component intermediate into the vacuum heat treatment furnace and evacuate to 1.5*10 -3 Pa, heat to 700℃~800℃ at a rate of 10~20℃ / min and adjust the vacuum degree in the furnace to keep the vacuum degree in the furnace higher than 3*10 -3 Pa, keep warm for 2 to 4 hours and then cool to room temperature at 5 to 15 °C / min.

[0027] It can be seen from the technical scheme of the present invention above that the friction stir additive manufacturing method of a titanium alloy component with nano-scale fine grain structure proposed by the present invention, under the premise of hydrogen solid solution, utilizes the large plastic deformation characteristics of the equal-diameter angular extrusion process to obtain nano-scale fine grains without changing the chemical composition of the material. After the equal-diameter angular extrusion process, the grain size is reduced, the grain boundary density is increased, the dislocation density within the grain is increased, and the coordination of grain rotation and sliding is enhanced. At the same time, the finer the grains, the better the equiaxility, the smaller the size and density of the voids produced, and the easier the sliding and rotation of the grains are, which improves the mechanical properties of the titanium alloy. On this basis, the friction stir additive manufacturing technology is combined to further refine the grains. Moreover, since the heat input of the friction stir process is greatly reduced, the expansion and contraction of the material during heating or cooling are not large, the degree of uneven deformation is very small, and the residual stress in the material is very small, thereby achieving the purpose of obtaining a nano-scale fine grain structure and good mechanical properties.

[0028] The present invention first changes the phase composition and microstructure of the titanium alloy through hydrogen solution treatment, so that the titanium alloy rod is in a state of low softening temperature and low flow stress. With the strong β-stabilizing effect of hydrogen, the phase transition point of the titanium alloy can be significantly reduced, the β-phase ratio can be increased, and the high-temperature rheological stress can be reduced, so that nanocrystals can be more easily obtained in the subsequent equal-channel angular extrusion, and the stability of the nanocrystals is improved in the stir friction additive manufacturing process, and a more stable and finer nanocrystal grain size is obtained; at the same time, the hydrogenation process can make the transition temperature of (α+β→β) show a downward trend, thereby reducing the hot working temperature, and can reduce the phase transition temperature of the titanium alloy by 100°C, which is beneficial to the realization of the equal-channel angular extrusion process and the temperature control in the stir friction additive manufacturing process, and reduces the processing stress of the titanium alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a process flow chart of the friction stir additive manufacturing method of the titanium alloy component with nano-scale fine grain structure of the present invention.

[0030] Figure 2 It is a process schematic diagram of equal-channel angular extrusion of the present invention.

[0031] Figure 3 It is a schematic diagram of the friction stir additive manufacturing process of the present invention.

[0032] Figure 4 a and Figure 4 b are microstructure diagrams of the titanium alloy after medium-diameter angular extrusion and the final workpiece in Example 1 of the present invention, respectively.

[0033] Figure 5 a and Figure 5 b are microstructure diagrams of the titanium alloy after medium-diameter angular extrusion and the final workpiece in Example 2 of the present invention, respectively.

[0034] Figure 6 a and Figure 6 b are microstructure diagrams of the titanium alloy after medium-diameter angular extrusion and the final workpiece in Example 3 of the present invention, respectively.

[0035] Figure 7 a and Figure 7 b are microstructure diagrams of the titanium alloy after medium-diameter angular extrusion and the final workpiece in comparative example 1 of the present invention, respectively.

[0036] Figure 8 a and Figure 8 b are microstructure diagrams of the titanium alloy after medium-diameter angular extrusion and the final workpiece in comparative example 2 of the present invention, respectively.

[0037] Fig. 9 a and Fig. 9 b are the microstructure diagrams of the titanium alloy after medium-diameter angular extrusion and the final workpiece in comparative example 3 of the present invention.

[0038] Fig.10 It is the microstructure diagram of the final workpiece in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0039] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.

[0040] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily intended to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways.

[0041] Titanium alloys have the characteristics of large yield strength ratio, high resistance to high temperature deformation, and low plasticity. Under normal circumstances, it is difficult to carry out the relevant severe plastic deformation process, and it is easy to be tool-friendly during processing; if nano-titanium alloys are obtained by high temperature severe plastic deformation, the nano-grains are also very easy to grow, and it is still difficult to prepare fine nano-crystalline structures in the end; and because titanium is highly chemically active, it is easy to combine with gas impurities. When the temperature is high, titanium is easily oxidized to form a brittle layer. Therefore, lowering the deformation temperature and improving the stability of the organization are the key to the formation of titanium alloy nanocrystals.

[0042] Therefore, combined with Figure 1As shown, the present invention provides a stir friction additive manufacturing method for a titanium alloy component with a nano-scale fine grain structure. First, the titanium alloy is placed in a state of low softening temperature and low flow stress through hydrogen treatment. After temporary hydrogen alloying, the diffusion of elements in the titanium alloy can be promoted, and the phase transition temperature can be significantly reduced. It has the ability of hydrogen-induced high-temperature plasticity, and can effectively reduce the processing stress of the titanium alloy, thereby improving the plasticity of the titanium alloy. Based on this, the equal-diameter angular extrusion process is used to achieve the grain refinement of the titanium alloy rod, and then combined with stir friction additive manufacturing to obtain a titanium alloy workpiece.

[0043] Since the previous hydrogenation treatment utilizes the strong β-stabilizing effect of hydrogen, the nanocrystals are well retained during the high-temperature and severe plastic deformation of the titanium alloy. Finally, the titanium alloy workpiece is annealed and dehydrogenated by heat treatment. By utilizing the reversibility of hydrogen in the titanium alloy, the unstable hydrides are decomposed under high temperature and vacuum conditions, and the hydrogen in the form of solid solution escapes to control the hydrogen content in the alloy, so as to ensure that the hydrogen content in the titanium alloy reaches the value specified in the safety use standard, avoid hydrogen embrittlement, and obtain titanium alloy parts with good microstructure and mechanical properties.

[0044] In a preferred embodiment of the present invention, a friction stir additive manufacturing method for a titanium alloy component having a nano-scale fine grain structure is provided, comprising the following steps:

[0045] The first titanium alloy rod is subjected to hydrogen treatment and high temperature solution treatment in sequence to obtain a second titanium alloy rod;

[0046] The second titanium alloy rod is subjected to equal-channel angular extrusion processing to refine the grain size of the titanium alloy to a first nano-grain range, thereby obtaining a third titanium alloy rod;

[0047] Using the third titanium alloy rod as a raw material, a friction stir additive manufacturing process is adopted, and deposition is performed layer by layer in an upward growth manner starting from the first layer according to a preset program until the last layer is deposited, thereby obtaining a titanium alloy component intermediate;

[0048] Annealing and dehydrogenation heat treatment are performed on the titanium alloy component intermediate to obtain a titanium alloy component with a nano-scale fine grain structure, and the grain size of the titanium alloy is within the second nano-grain range;

[0049] Among them, hydrogen treatment and solid solution treatment reduce the processing stress of titanium alloy and improve the stability of titanium alloy structure.

[0050] In an optional manner, the first nano-grain interval is (200nm, 500nm].

[0051] In an optional manner, the second nano-grain interval is [50nm, 200nm].

[0052] In an optional manner, the specific process of hydrogenation treatment includes:

[0053] The first titanium alloy rod is placed in a tubular hydrogen heat treatment furnace and vacuumed to 1.5*10 -3 Pa, heat to 700°C-800°C at a rate of 10-20°C / min, keep warm for 10-30min, then fill with 0.1-0.8% hydrogen according to the weight percentage of the titanium alloy rod, keep warm for 1-4h, and then cool to room temperature at a rate of 5-15°C / min.

[0054] In the optional method, the specific process of high temperature solution treatment includes:

[0055] The first titanium alloy rod after hydrogen treatment is placed in a heat treatment furnace and heated at a rate of 10-20°C / min to the titanium alloy phase transition temperature T p ℃+10℃, keep warm for 20-40min, and then quickly cool to room temperature by water cooling to obtain the second titanium alloy rod.

[0056] In an optional manner, the specific process of equal channel angular extrusion processing includes:

[0057] The second titanium alloy rod is preheated to 600°C at a rate of 10-20°C / min and kept warm for at least 20 minutes. The equal-diameter angular extrusion die is heated to 350°C at a rate of 10-20°C / min, and the preheated second titanium alloy rod is immediately transferred to the equal-diameter angular extrusion die. The second titanium alloy rod is extruded in one pass at a rate of 5-10 mm / s under the extrusion action of the die.

[0058] In an alternative approach, the inner corner of the mold is used The die with a range of 90 to 130° and a die external angle ψ of 0 to 30° is subjected to equal-diameter angular extrusion.

[0059] In an optional manner, the process parameters of the friction stir additive manufacturing include:

[0060] Stirring head forward speed: 100~2000mm / min; Stirring head rotation speed: 500~3000r / mm; Feeding speed: 1~200mm / min; Stirring head downward pressure: 10~500KN; Stirring head pressure: 0.1~10mm.

[0061] In an optional manner, the specific process of annealing and dehydrogenation heat treatment includes:

[0062] Put the titanium alloy component intermediate into the vacuum heat treatment furnace and evacuate to 1.5*10 -3 Pa, heat to 700℃~800℃ at a rate of 10~20℃ / min and adjust the vacuum degree in the furnace to keep the vacuum degree in the furnace higher than 3*10-3 Pa, keep warm for 2 to 4 hours and then cool to room temperature at 5 to 15 °C / min.

[0063] As an example of the present invention, a friction stir additive manufacturing method for a titanium alloy component with a nano-scale fine grain structure includes the following specific processes:

[0064] Step 1: Place the titanium alloy rod in a tubular hydrogen heat treatment furnace and evacuate to 1.5*10 -3 Pa, heating to 700°C-800°C at a speed of 10-20°C / min, keeping warm for 10-30min, filling with 0.1%-0.8% hydrogen according to the weight percentage of the titanium alloy rod, keeping warm for 1-4h, and then cooling to room temperature at a speed of 5-15°C / min, to obtain a hydrogenated titanium alloy rod;

[0065] Step 2: Place the hydrogenated titanium alloy bar into a heat treatment furnace and heat it at a rate of 10-20°C / min to the phase transition temperature T p ℃+10℃, keep warm for 20min~40min, then quickly cool to room temperature through water cooling;

[0066] Step 3: Combine Figure 2 As shown, the titanium alloy rod 1 after solid solution and the equal-diameter angular extrusion die 2 are placed in a heat treatment furnace for preheating. When the temperature of the titanium alloy rod reaches 600°C, it is kept warm for 20 minutes. When the temperature of the die reaches 350°C, the titanium alloy rod 1 is immediately transferred from the heat treatment furnace to the equal-diameter angular extrusion die 2 (the inner angle of the die is 90°, and the outer angle of the die is 30°), and the hydraulic device 3 is used to extrude the titanium alloy rod from the die at a speed of 10 mm / s.

[0067] Step 4: Use the titanium alloy rod that has undergone equal-diameter angular extrusion for friction stir additive manufacturing, select the process parameters of stroke (forward) speed of 100-2000 mm / min, stirring head speed of 500-3000 r / mm, feeding speed of 1-200 mm / min, stirring head down pressure: 10-500 KN, and stirring head pressure of 0.1-10 mm for forming processing to obtain a titanium alloy workpiece.

[0068] In a preferred embodiment, Figure 3 As shown, the structure of the stirring head 4 used for stirring and friction treatment can adopt the existing stirring and friction head structure, and set a channel for a cylindrical metal rod 1 in the center, send the metal rod to the lower position of the stirring head 4, and stir and friction treatment is performed through the stirring needle set at the lower end of the stirring head 4.

[0069] Combination Figure 3The illustrated embodiment exemplarily shows an example of providing a channel for a cylindrical metal rod in the stirring head 4 and depositing the deposition layer 7 layer by layer on the substrate 6 in an upward growth manner.

[0070] Step 5: Anneal and dehydrogenate the titanium alloy workpiece: Place the titanium alloy workpiece in a vacuum heat treatment furnace and evacuate to 1.5*10 -3 Pa, heat to 700℃~800℃ at a rate of 10~20℃ / min and adjust the vacuum degree in the furnace to keep the vacuum degree in the furnace higher than 3*10 -3 Pa, keep warm for 2 to 4 hours and then cool to room temperature at 5 to 15 °C / min.

[0071] For better understanding, the present invention is further described below in conjunction with several specific examples, but the processing technology is not limited thereto, and the content of the present invention is not limited thereto.

[0072] The following Examples 1-3 are all described by taking different types (TA2, TB5, TC4) of titanium alloy as examples, and titanium alloy bars are subjected to specific operation steps to obtain a 100 mm×80 mm×8 mm rectangular titanium alloy workpiece.

[0073] Example 1

[0074] The actual composition of TA2 titanium alloy is shown in Table 1

[0075] Table 1

[0076] Ti Fe Sn Si C N Al H O Actual ingredients the remaining 0.30 2.0 0.15 0.1 0.05 4.0 0.015 0.2

[0077] Step 1: Place the titanium alloy rod (12 mm in diameter and 60 mm in length) in a tubular hydrogen heat treatment furnace and evacuate to 1.5*10 -3 Pa, heated to 800°C at a rate of 15°C / min, kept warm for 25 minutes, filled with 0.8% hydrogen according to the weight percentage of the titanium alloy rod, kept warm for 3 hours, and then cooled to room temperature at a rate of 15°C / min to obtain the hydrogenated titanium alloy rod.

[0078] Step 2: Place the titanium alloy rod treated in step 1 into a heat treatment furnace, heat to 650°C at a rate of 20°C / min, keep warm for 30 minutes, and then quickly cool to room temperature through water cooling.

[0079] Step 3, place the titanium alloy rod treated in step 2 and the equal-diameter angular extrusion die into a heat treatment furnace for preheating. When the temperature of the titanium alloy rod reaches 600°C, keep it warm for 30 minutes. When the temperature of the die reaches 350°C, immediately transfer the titanium alloy rod from the heat treatment furnace to an equal-diameter angular extrusion die with an inner angle of 90° and an outer angle of 30°. Use a hydraulic device to extrude the titanium alloy rod from the die at a speed of 10 mm / s with a force of 5000KN.

[0080] Step 4: Use the titanium alloy rod that has undergone equal-diameter angular extrusion for friction stir additive manufacturing, and select the process parameters of stroke (forward) speed of 800 mm / min, stirring head speed of 1500 r / mm, feeding speed of 100 mm / min, stirring head pressure of 1.0 mm, and downward pressure of 300 KN for forming processing to obtain a titanium alloy workpiece.

[0081] Step 5: Dehydrogenate and anneal the titanium alloy workpiece; place the titanium alloy workpiece in a vacuum heat treatment furnace and evacuate to 1.5*10 -3 Pa, heated to 750℃ at a rate of 20℃ / min, and maintained the vacuum degree in the furnace higher than 3*10 -3 Pa, keep warm for 3 h and then cool to room temperature at 10 °C / min.

[0082] Example 2

[0083] The actual composition of TB5 titanium alloy is shown in Table 2

[0084] Table 2

[0085] Ti Fe Sn C N Cr Al H V Actual ingredients the remaining 0.25 2.5 0.05 0.05 2.5 2.8 0.015 14.0

[0086] Step 1: Place the titanium alloy rod (12 mm in diameter and 60 mm in length) in a tubular hydrogen heat treatment furnace and evacuate to 1.5*10 -3 Pa, heated to 800°C at a rate of 20°C / min, kept warm for 30 minutes, filled with 0.8% hydrogen according to the weight percentage of the titanium alloy rod, kept warm for 4 hours, and then cooled to room temperature at a rate of 15°C / min to obtain the hydrogenated titanium alloy rod.

[0087] Step 2: Place the titanium alloy rod treated in step 1 into a heat treatment furnace, heat to 700°C at a rate of 20°C / min, keep warm for 30 minutes, and then quickly cool to room temperature through water cooling.

[0088] Step 3, place the titanium alloy rod treated in step 2 and the equal-diameter angular extrusion die into a heat treatment furnace for preheating. When the temperature of the titanium alloy rod reaches 600°C, keep it warm for 20 minutes. When the temperature of the die reaches 350°C, immediately transfer the titanium alloy rod from the heat treatment furnace to an equal-diameter angular extrusion die with an inner angle of 90° and an outer angle of 30°. Use a hydraulic device to extrude the titanium alloy rod from the die at a speed of 10 mm / s with a force of 5000KN.

[0089] Step 4: Use the titanium alloy rod that has undergone equal-diameter angular extrusion for friction stir additive manufacturing, and select the process parameters of a stroke (forward) speed of 600 mm / min, a stirring head speed of 1200 r / mm, a feeding speed of 80 mm / min, a stirring head pressure of 0.8 mm, and a downward pressure of 280 KN for forming processing to obtain a titanium alloy workpiece.

[0090] Step 5: Dehydrogenate and anneal the titanium alloy workpiece: Place the titanium alloy workpiece into a vacuum heat treatment furnace and evacuate to 1.5*10 -3 Pa, heated to 750℃ at a rate of 20℃ / min, and maintained the vacuum degree in the furnace higher than 3*10 -3 Pa, keep warm for 3 h and then cool to room temperature at 10 °C / min.

[0091] Example 3

[0092] The actual composition of TC4 titanium alloy is shown in Table 3

[0093] Table 3

[0094] Ti Fe C N H O Al V Actual ingredients Residue 0.30 0.10 0.05 0.015 0.20 5.5 3.5

[0095] Step 1: Place the titanium alloy rod (12 mm in diameter and 60 mm in length) in a tubular hydrogen heat treatment furnace and evacuate to 1.5*10 -3 Pa, heated to 750°C at a rate of 15°C / min, kept warm for 20 minutes, filled with 0.55% hydrogen according to the weight percentage of the titanium alloy rod, kept warm for 3 hours, and then cooled to room temperature at a rate of 10°C / min to obtain the hydrogenated titanium alloy rod.

[0096] Step 2: Place the titanium alloy rod treated in step 1 into a heat treatment furnace, heat to 900°C at a rate of 15°C / min, keep warm for 30 minutes, and then quickly cool to room temperature through water cooling.

[0097] Step 3, place the titanium alloy rod treated in step 2 and the equal-diameter angular extrusion die into a heat treatment furnace for preheating. When the temperature of the titanium alloy rod reaches 600°C, keep it warm for 20 minutes. When the temperature of the die reaches 350°C, immediately transfer the titanium alloy rod from the heat treatment furnace to an equal-diameter angular extrusion die with an inner angle of 90° and an outer angle of 30°. Use a hydraulic device to extrude the titanium alloy rod from the die at a speed of 10 mm / s with a force of 5000KN.

[0098] Step 4: Use the titanium alloy rod that has undergone equal-diameter angular extrusion for friction stir additive manufacturing, and select the process parameters of a stroke (forward) speed of 500 mm / min, a stirring head speed of 1000 r / mm, a feeding speed of 60 mm / min, a stirring head pressure of 0.5 mm, and a downward pressure of 260 KN for forming processing to obtain a titanium alloy workpiece.

[0099] Step 5: Dehydrogenate and anneal the titanium alloy workpiece: Place the titanium alloy workpiece into a vacuum heat treatment furnace and evacuate to 1.5*10 -3 Pa, heated to 750℃ at a rate of 20℃ / min, and maintained the vacuum degree in the furnace higher than 3*10 -3 Pa, keep warm for 3 h and then cool to room temperature at 10 °C / min.

[0100] Comparative Example 1

[0101] The composition of the TA2 titanium alloy used in Comparative Example 1 is consistent with that in Example 1.

[0102] Step 1. Place the titanium alloy rod and the equal-diameter angular extrusion die in a heat treatment furnace for preheating. When the temperature of the titanium alloy rod reaches 700°C, keep it warm for 30 minutes. When the temperature of the die reaches 350°C, immediately transfer the titanium alloy rod from the heat treatment furnace to an equal-diameter angular extrusion die with an inner angle of 90° and an outer angle of 30°. Use a hydraulic device to extrude the titanium alloy rod from the die at a speed of 8 mm / s with a force of 6000KN.

[0103] Step 2: Use the titanium alloy rod that has undergone equal-diameter angular extrusion for friction stir additive manufacturing, and select the process parameters of a stroke (forward) speed of 500 mm / min, a stirring head speed of 2000 r / mm, a feeding speed of 70 mm / min, a stirring head pressure of 3 mm, and a downward pressure of 400 KN for forming processing to obtain a titanium alloy workpiece.

[0104] Step 3: Dehydrogenate and anneal the titanium alloy workpiece; place the titanium alloy workpiece in a vacuum heat treatment furnace and evacuate to 1.5*10 -3 Pa, heated to 750℃ at a rate of 20℃ / min, and maintained the vacuum degree in the furnace higher than 3*10 -3Pa, keep warm for 3 h and then cool to room temperature at 10 °C / min.

[0105] Comparative Example 2

[0106] The composition of the TB5 titanium alloy used in Comparative Example 1 is consistent with that in Example 2.

[0107] Step 1. Place the titanium alloy rod and the equal-diameter angular extrusion die in a heat treatment furnace for preheating. When the temperature of the titanium alloy rod reaches 700°C, keep it warm for 20 minutes. When the temperature of the die reaches 350°C, immediately transfer the titanium alloy rod from the heat treatment furnace to an equal-diameter angular extrusion die with an inner angle of 90° and an outer angle of 30°. Use a hydraulic device to extrude the titanium alloy rod from the die at a speed of 8 mm / s with a force of 6000KN.

[0108] Step 2: Use the titanium alloy rod that has been subjected to equal-diameter angular extrusion for friction stir additive manufacturing, and select the process parameters of a stroke (forward) speed of 400 mm / min, a stirring head speed of 1800 r / mm, a feeding speed of 50 mm / min, a stirring head pressure of 2.8 mm, and a downward pressure of 400 KN for forming processing to obtain a titanium alloy workpiece.

[0109] Step 3: Dehydrogenate and anneal the titanium alloy workpiece: Place the titanium alloy workpiece into a vacuum heat treatment furnace and evacuate to 1.5*10 -3 Pa, heated to 750℃ at a rate of 20℃ / min, and maintained the vacuum degree in the furnace higher than 3*10 -3 Pa, keep warm for 3h and then cool to room temperature at 10℃ / min

[0110] Comparative Example 3

[0111] The composition of the TC4 titanium alloy used in Comparative Example 1 is consistent with that in Example 3.

[0112] Step 1. Place the titanium alloy rod and the equal-diameter angular extrusion die in a heat treatment furnace for preheating. When the temperature of the titanium alloy rod reaches 700°C, keep it warm for 20 minutes. When the temperature of the die reaches 350°C, immediately transfer the titanium alloy rod from the heat treatment furnace to an equal-diameter angular extrusion die with an inner angle of 90° and an outer angle of 30°. Use a hydraulic device to extrude the titanium alloy rod from the die at a speed of 8 mm / s with a force of 6000KN.

[0113] Step 2: Use the titanium alloy rod that has been subjected to equal-diameter angular extrusion for friction stir additive manufacturing, and select the process parameters of a stroke (forward) speed of 300 mm / min, a stirring head speed of 1600 r / mm, a feeding speed of 40 mm / min, a stirring head pressure of 2.5 mm, and a downward pressure of 500 KN for forming processing to obtain a titanium alloy workpiece.

[0114] Step 3: Dehydrogenate and anneal the titanium alloy workpiece: Place the titanium alloy workpiece into a vacuum heat treatment furnace and evacuate to 1.5*10 -3 Pa, heated to 750℃ at a rate of 20℃ / min, and maintained the vacuum degree in the furnace higher than 3*10 -3 Pa, keep warm for 3 h and then cool to room temperature at 10 °C / min.

[0115] Comparative Example 4

[0116] The composition of the TA2 titanium alloy used in Comparative Example 4 is consistent with that in Example 1.

[0117] Step 1: Use the titanium alloy rod for friction stir additive manufacturing, select the process parameters of stroke (forward) speed of 300 mm / min, stirring head speed of 2000 r / mm, feeding speed of 40 mm / min, stirring head pressure of 3 mm, and downward pressure of 500 KN for forming processing to obtain a titanium alloy workpiece.

[0118] Step 2: Dehydrogenate and anneal the titanium alloy workpiece; place the titanium alloy workpiece in a vacuum heat treatment furnace and evacuate to 1.5*10 -3 Pa, heated to 750℃ at a rate of 20℃ / min, and maintained the vacuum degree in the furnace higher than 3*10 -3 Pa, keep warm for 3 h and then cool to room temperature at 10 °C / min.

[0119] Performance Testing

[0120] The metallurgical structures and mechanical properties of the titanium alloys finally obtained by printing using the processes of the above-mentioned embodiments 1-3 and comparative examples 1-4 are shown in Table 4.

[0121] Table 4 Mechanical properties and average grain size data of titanium alloy workpieces

[0122]

[0123] Combining the preparation process and the results in Table 4, it can be seen that during the process treatment, hydrogenation can effectively reduce the temperature requirements required for equal channel angular extrusion and friction stir additive manufacturing, and has an important influence on the processes of equal channel angular extrusion and friction stir additive manufacturing. When the hydrogenation process is not adopted, the titanium alloy has high strength and poor plasticity, and obviously requires more intense stirring parameters to achieve extrusion and forming of the rod.

[0124] contrast Figure 4 a. Figure 4 b and Fig.10 , and combined with Figure 5 a. Figure 5 b. Figure 6 a. Figure 6 b. Figure 7 a. Figure 7 b. Figure 8 a. Figure 8 b. Fig. 9 a. Fig. 9 As shown in b, it can be seen that the equal-channel angular extrusion process and the friction stir additive manufacturing technology can effectively realize the nano-sizing of the titanium alloy grain structure without changing the material composition, and the pre-hydrogenation process can be used to stably retain the nanocrystals in the workpiece.

[0125] It can be seen from the metallographic micrographs of the comparative examples that when hydrogen solution treatment is not adopted, even if the titanium alloy forms fine grain strengthening through plastic deformation, some columnar crystals are formed in the structure under the action of high temperature, and the nanocrystals produced by the equal-channel angular pressing process cannot be stably retained; and when hydrogen solution treatment is not performed, the nanocrystal grain size obtained after equal-channel angular pressing is larger, indicating that hydrogen solution treatment is more conducive to obtaining nanocrystals; and the titanium alloy workpiece obtained by direct stir friction additive manufacturing cannot obtain nanocrystalline structure.

[0126] It can be seen from the above that the process of the invention can be used to obtain a nano-grade titanium alloy workpiece and the workpiece has good mechanical properties.

[0127] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A friction stir additive manufacturing method for a titanium alloy component having a nano-scale fine grain structure, characterized in that: The following steps are involved: The first titanium alloy rod is subjected to hydrogen treatment and high-temperature solution treatment in sequence to obtain a second titanium alloy rod; wherein the hydrogen treatment is to place the first titanium alloy rod in a heat treatment furnace, introduce hydrogen gas in a certain percentage of the weight of the first titanium alloy rod, and then perform heat preservation treatment, and then cool to room temperature; The second titanium alloy rod is subjected to equal-channel angular extrusion processing to refine the grain size of the titanium alloy to a first nano-grain range, thereby obtaining a third titanium alloy rod; wherein the first nano-grain range is (200nm, 500nm]; Using the third titanium alloy rod as a raw material, a friction stir additive manufacturing process is adopted, and deposition is performed layer by layer in an upward growth manner starting from the first layer according to a preset program until the last layer is deposited, thereby obtaining a titanium alloy component intermediate; Annealing and dehydrogenation heat treatment are performed on the titanium alloy component intermediate to obtain a titanium alloy component with a nano-scale fine grain structure, and the grain size of the titanium alloy is in a second nano-grain range; wherein the second nano-grain range is [50nm, 200nm]; Among them, hydrogen treatment and solid solution treatment reduce the processing stress of titanium alloy and improve the stability of titanium alloy structure.

2. The friction stir additive manufacturing method for a titanium alloy component having a nano-scale fine grain structure according to claim 1, characterized in that: The specific process of hydrogen treatment includes: The first titanium alloy rod is placed in a tubular hydrogen heat treatment furnace and vacuumed to 1.5*10 -3 Pa and then heated to 700℃~800℃ at a rate of 10~20℃ / min. After keeping warm for 10~30min, 0.1~0.8% hydrogen is filled in according to the weight percentage of the titanium alloy rod. After keeping warm for 1~4h, it is cooled to room temperature at a rate of 5~15℃ / min.

3. The friction stir additive manufacturing method for a titanium alloy component having a nano-scale fine grain structure according to claim 1, characterized in that: The specific process of high temperature solution treatment includes: The first titanium alloy rod after hydrogen treatment is placed in a heat treatment furnace and heated at a rate of 10-20°C / min to the titanium alloy phase transition temperature T p ℃+10℃, keep warm for 20~40min, and then quickly cool to room temperature by water cooling to obtain the second titanium alloy rod.

4. The friction stir additive manufacturing method for a titanium alloy component having a nano-scale fine grain structure according to claim 1, characterized in that: The specific processes of equal channel angular extrusion processing include: The second titanium alloy rod is preheated to 600°C at a rate of 10-20°C / min and kept warm for at least 20 minutes. The equal-diameter angular extrusion die is heated to 350°C at a rate of 10-20°C / min, and the preheated second titanium alloy rod is immediately transferred to the equal-diameter angular extrusion die. The second titanium alloy rod is extruded in one pass at a rate of 5-10 mm / s under the extrusion action of the die.

5. The friction stir additive manufacturing method for a titanium alloy component having a nano-scale fine grain structure according to claim 1, characterized in that: The equal-diameter angular extrusion process is performed using a die with a die inner angle φ ranging from 90 to 130° and a die outer angle ψ ranging from 0 to 30°.

6. The friction stir additive manufacturing method for a titanium alloy component having a nano-scale fine grain structure according to claim 1, characterized in that: The process parameters for Friction Stir Additive Manufacturing include: Stirring head forward speed: 100~2000mm / min; Stirring head rotation speed: 500~3000r / mm; Feeding speed: 1~200mm / min; Stirring head downward pressure: 10~500KN; Stirring head pressure: 0.1~10mm.

7. The friction stir additive manufacturing method for a titanium alloy component having a nano-scale fine grain structure according to claim 1, characterized in that: The specific processes of annealing and dehydrogenation heat treatment include: Put the titanium alloy component intermediate into the vacuum heat treatment furnace and evacuate to 1.5*10 -3 Pa, heat to 700℃~800℃ at a rate of 10~20℃ / min and adjust the vacuum degree in the furnace to keep the vacuum degree in the furnace higher than 3*10 -3 Pa, keep warm for 2~4h, then cool to room temperature at 5~15℃ / min.

Citation Information

Patent Citations

  • Preparation method of ultrafine-grain titanium matrix composite material by using mushy-zone titanium alloy as matrix

    CN103820744A

  • Friction stir welding additive manufacture method of bar material

    CN105397276A

  • Process for improving titanium alloy wire additive manufacturing metallurgical structure

    CN113430474A

  • Process for improving titanium alloy bar stirring friction additive manufacturing metallurgical structure

    CN116288090A

  • Preparation method of high-strength TC4 pipe

    CN116689531A